Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1093/rheumatology/kez030
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity of biologic agents in juvenile idiopathic arthritis: a systematic review and meta-analysis

Abstract: Objective The clinical impact of anti-drug antibodies (ADAbs) in paediatric patients with JIA remains unknown. This systematic review and meta-analysis aimed to summarize the prevalence of ADAbs in JIA studies; investigate the effect of ADAbs on treatment efficacy and adverse events; and explore the effect of immunosuppressive therapy on antibody formation. Methods PubMed, Embase and the Cochrane Library were systematically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 55 publications
2
46
0
5
Order By: Relevance
“…ADA formation is a well-recognized impediment to mAbbased therapies in pediatric indications, such as juvenile idiopathic arthritis (JIA) [50]. The current literature suggests no significant difference in immunogenicity between adults and pediatric populations for most investigated mAbs, including etanercept, infliximab, and tocilizumab [3].…”
Section: Immunogenicitymentioning
confidence: 99%
“…ADA formation is a well-recognized impediment to mAbbased therapies in pediatric indications, such as juvenile idiopathic arthritis (JIA) [50]. The current literature suggests no significant difference in immunogenicity between adults and pediatric populations for most investigated mAbs, including etanercept, infliximab, and tocilizumab [3].…”
Section: Immunogenicitymentioning
confidence: 99%
“…In adults, antibodies against mAb reduces the efficacy of treatment and increases the risk of HSR, especially for infliximab [39][40][41][42]. A meta-analysis [43] on the immunogenicity of mAbs used for JIA showed that all mAbs induced antibodies: abatacept in 2.3-23.3% of cases, adalimumab 10.9-37%, anakinra 81.8%, canakinumab 3.1%, etanercept 0-21.9%, golimumab 46.8%, infliximab 36.6%, tocilizumab 0.5-7.5%, with a total pooled prevalence of 16.9%. In 4 of 20 patients treated with infliximab who had antibodies to infliximab, a possible anaphylactic reaction was observed, while none occurred in those who had lacked infliximab antibodies.…”
Section: Infliximabmentioning
confidence: 99%
“…The formation of ADA is documented with all the licensed biologic treatments in JIA. However, the relation between ADA and treatment failure or adverse effects, the persistent or transient nature of ADA, as well as their prevalence in relation to treatment duration, vary across the different biologics ( Doeleman et al, 2019 ). For instance, antibodies against etanercept, abatacept and canakinumab are non-neutralizing and are not linked with loss of efficacy ( Mori et al, 2012 ; Sun et al, 2016 ; Doeleman et al, 2019 ; Verstegen et al, 2020 ).…”
Section: Therapeutic Drug Monitoring and Anti-drug Antibodies As Biommentioning
confidence: 99%
“…However, the relation between ADA and treatment failure or adverse effects, the persistent or transient nature of ADA, as well as their prevalence in relation to treatment duration, vary across the different biologics ( Doeleman et al, 2019 ). For instance, antibodies against etanercept, abatacept and canakinumab are non-neutralizing and are not linked with loss of efficacy ( Mori et al, 2012 ; Sun et al, 2016 ; Doeleman et al, 2019 ; Verstegen et al, 2020 ). Similarly, despite the increased prevalence of ADA in patients treated with anakinra (82% at 12 months), the majority of patients develop non-neutralizing antibodies and do not lose treatment response ( Lovell et al, 2000 ; Ilowite et al, 2009 ).…”
Section: Therapeutic Drug Monitoring and Anti-drug Antibodies As Biommentioning
confidence: 99%
See 1 more Smart Citation